The effects of telepresence with real-time video and audio communication on parent-infant interaction and staff experience in neonatal intensive care unit - Tomoko Saito; Tomoyuki Shimokaze; Miku Niizuma; Masako Suzuki; Makiko Toyoshima; Katsuaki Toyoshima (Elsevier, 2024)
Objective: We implemented an online visitation system named "telepresence" in the neonatal intensive care unit (NICU) for family members at home to communicate with their babies in real-time using video and audio. This study evaluated the impact of this system on families and medical staff. Methods: Nineteen families of babies admitted to the NICU between 2022 and 2023 and 65 medical staff participated. Each family experienced two weeks of virtual visits. Changes in parental depression and attachment were assessed. Result: Before and after telepresence, the median Edinburgh Postnatal Depression Scale score reduced from 6 to 4 (p = 0.026), and the Mother-to-Infant Bonding Scale score showed a decreasing trend, with both medians at 2 (p = 0.057). Eighty-nine percent of the parents and 97% of staff reported that telepresence did not increase parental stress, and 88% of parents felt positive changes in their baby's siblings. All parents wanted to visit their babies in person after seeing them on camera. Conclusion: Telepresence improved parental mental health, reduced family distress, and supported connection with their infants, making them eager to visit in person. Innovations: This technology potentially make parents want to visit more by helping them feel more connected to their infants.